Answer:
![\boxed{D. \: 40\degree}](https://tex.z-dn.net/?f=%20%5Cboxed%7BD.%20%5C%3A%2040%5Cdegree%7D%20)
Step-by-step explanation:
<em>Angle sum property of triangle states that the sum of interior angles of a triangle is 180°</em>
So,
![= > 2y \degree + (y + 10)\degree + 50\degree = 180\degree \\ \\ = > 2y\degree + y\degree + 10\degree + 50\degree = 180\degree \\ \\ = > 3y\degree + 60\degree = 180\degree \\ \\ = > 3y\degree = 180\degree - 60\degree \\ \\ = > 3y\degree = 120\degree \\ \\ = > y = \frac{120\degree}{3\degree} \\ \\ = > y = 40\degree](https://tex.z-dn.net/?f=%20%3D%20%20%3E%202y%20%5Cdegree%20%2B%20%28y%20%2B%2010%29%5Cdegree%20%2B%2050%5Cdegree%20%3D%20180%5Cdegree%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%202y%5Cdegree%20%2B%20y%5Cdegree%20%2B%2010%5Cdegree%20%2B%2050%5Cdegree%20%3D%20180%5Cdegree%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%203y%5Cdegree%20%2B%2060%5Cdegree%20%3D%20180%5Cdegree%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%203y%5Cdegree%20%3D%20180%5Cdegree%20-%2060%5Cdegree%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%203y%5Cdegree%20%3D%20120%5Cdegree%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%20y%20%3D%20%20%5Cfrac%7B120%5Cdegree%7D%7B3%5Cdegree%7D%20%20%5C%5C%20%20%5C%5C%20%20%3D%20%20%3E%20y%20%3D%2040%5Cdegree%20)
22.7%
Given that last year stock for company A was $7200
The stock for company B last year was worth $3510
Stock in company A decreased by 24%
This means the new value of stock for company A became;
(100-24)/100 *$7200
76/100*$7200
0.76*7200 =$5472
Stock in company B decreased by 20%
This means the new value of stock for company B became;
(100-20)/100 *$3510
80/100*$3510
0.8*$3510
$2808
Original investors stock value was = $7200+$3510 =$10710
New investors stock value is = $5472+$2808=$8280
Decrease in value of stock = $10710-$8280 =$2430
percentage decrease in stock value = decrease in stock/original value of stock *100%
=2430/10710 *100 =22.689
=22.7%
Someone else had the same problem answered
So here it is
Because
![\frac{f(x)}{x-3} = 2x^{2} + 10x - 1](https://tex.z-dn.net/?f=%20%5Cfrac%7Bf%28x%29%7D%7Bx-3%7D%20%3D%202x%5E%7B2%7D%20%2B%2010x%20-%201)
therefore
f(x) = (x-3)(2x² + 10x - 1) + k, where k = constant.
Because f(3) = 4, therefore k =4.
The polynomial is
f(x) = 2x³ + 10x² - x - 6x² - 30x + 3 + 4
= 2x³ + 4x² - 31x + 7
Answer: f(x) = 2x³ + 4x² - 31x + 7
Answer:
Step-by-step explanation:
221
Answer:
dissect the trapezium into a square and triangle. since the triangle is a right angled one the base is 17-7=10cm
the height is found using Pythagorean theorem to be 24cm i.e 26²=x²+10²,x=√(676-100),x=√576,x=24cn
area of trapezium is (1/2)(a+b)h
a is the shorter side and b the longer side
(1/2)*(7+17)24
=288cm²